Antenna Beam Steering using Sectorized Square EBG - Mohamad Isa, Mohd Sa'ari; Awang Md Isa, Azmi; Mohd Zin, Mohd Shahril Izuan; Mohd Johar, Fauzi; Zakaria, Zahriladha (Penerbit Universiti, UTeM, 2012)
In this paper, a pattern diversity antenna using a switched sectorized square mushroom like electromagnetic band gap (EBG) surface is presented. A low profile antenna is integrated with an EBG whose band stop and band pass properties are changed by switching vias in and out of sectors. The propagation characteristics and pattern directivity have been analyzed using CST Microwave Studio (CST MWS). The antenna radiation pattern has been steered in multiple directions as surface impedance in each sectors has been altered. The radiation pattern has been directed towards the EBG sectors with lower surface and reflected from the high impedance surface of EBG. The concept of the directive antenna using mushroom type EBG has been achieved with lower profile with compared to monopole type of parasitic pattern directive antenna.